Perovskite solar cells and manufacturing methods

The use of a passivation layer with aza-fused bicyclic compounds and organic salts in perovskite solar cells addresses instability issues by effectively passivating defects, enhancing efficiency and stability.

JP2024546528AActive Publication Date: 2024-12-25CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024536255
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2021-12-31
Publication Date
2024-12-25
Estimated Expiration
2041-12-31

AI Technical Summary

Technical Problem

Perovskite solar cells face instability due to deep-level and shallow-level defects, which affect efficiency and long-term stability, and conventional passivating agents like monocyclic organic small molecule amines are insufficiently effective.

Method used

A passivation layer containing an aza-fused bicyclic compound and/or an organic salt formed from an aza-fused bicyclic compound and an acid is applied to the perovskite layer, using a poor solvent and annealing process to form a passivation layer that effectively passivates defects at grain boundaries and surfaces.

Benefits of technology

The proposed passivation layer enhances the efficiency and stability of perovskite solar cells by preventing decomposition and volatilization of A-site cations, reducing internal resistance, and improving hydrophobicity, thereby increasing the long-term stability and performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024546528000001_ABST
    Figure 2024546528000001_ABST
Patent Text Reader

Abstract

The present invention provides a perovskite solar cell including at least an electrode, an electron transport layer, a hole transport layer, a perovskite layer, and a passivation layer, wherein the passivation layer contains a passivation agent, the passivation agent including an aza-fused bicyclic compound and / or an organic salt formed from the aza-fused bicyclic compound and an acid, each fused ring of the aza-fused bicyclic compound is independently a five- or six-membered saturated, unsaturated, or aromatic ring, and the fused ring of the aza-fused bicyclic compound includes 1 to 5 nitrogen atoms, and the fused ring is either an unsubstituted ring or substituted with 1 or 2 substituents having 1 to 3 carbon atoms.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a perovskite solar cell with improved stability and a method for manufacturing a perovskite solar cell. [Background technology]

[0002] As the mitigation of global warming and the construction of an eco-friendly civilization are receiving increasing attention, the diversification of energy and the development of green energy are also attracting more and more attention. Here, photovoltaic power generation, which converts solar energy into electrical energy, is becoming more and more widely used because it does not emit carbon during energy conversion and has a high degree of freedom in equipment installation. However, the current mainstream photovoltaic power generation device is a silicon-based solar cell panel using monocrystalline silicon or polycrystalline silicon, and this silicon-based solar cell panel has problems such as a large cell panel weight, a complicated production process, and high energy consumption and cost during the production process.

[0003] To solve the above problems, solar cells that can be manufactured by solution processes have been proposed. Among them, solar cells that contain a perovskite crystal structure as a light conversion layer have attracted much attention because their conversion efficiency is close to that of silicon-based solar cells.

[0004] However, the perovskite crystal structure is fragile and it is difficult to maintain a constant lattice shape for a long period of time under the usage environment, which is a factor that significantly affects the lifespan of perovskite solar cells.

[0005] In order to improve the stability of the perovskite crystal, CN106062983A proposes to further form a passivation layer containing a passivation agent such as thiophene or pyridine on the precipitated perovskite layer when manufacturing a perovskite solar cell. However, the present inventors found that there is room for improvement in the selection of the passivation agent in the prior art.

[0006] In addition, in the prior art, the method of forming a passivation layer generally involves applying a solution containing a perovskite precursor onto a layer carrying a perovskite layer, then applying a poor solvent to extract the perovskite solvent, precipitating a perovskite structure, removing excess solvent by heating, transforming the perovskite into an effective perovskite phase, applying a passivation agent to the perovskite surface, and finally annealing to remove the solvent, thereby forming a passivation layer on the perovskite layer. However, there is room for further simplification of the method of generating such a passivation layer. Summary of the Invention [Problem to be solved by the invention]

[0007] During the manufacturing process and device operation of perovskite solar cells, deep level and shallow level defects exist, which seriously affect the efficiency and long-term stability of the cell. Experiments have found that organic small molecule ammonium salts can passivate the defects on the perovskite surface and improve the device efficiency and stability. However, most of the current passivation agents are single-ring organic small molecule amines, which are not yet effective in improving the cell device efficiency and stability.

[0008] The problem to be solved by the present invention is to provide a perovskite solar cell including a passivation layer that is more effective in improving cell efficiency and stability, and a method for manufacturing a perovskite solar cell containing the passivation layer. [Means for solving the problem]

[0009] One aspect of the present invention is a perovskite solar cell comprising at least an electrode, an electron transport layer, a hole transport layer, a perovskite layer, and a passivation layer, The passivation layer contains a passivation agent, which includes an aza-fused bicyclic compound and / or an organic salt formed from an aza-fused bicyclic compound and an acid, and each fused ring of the aza-fused bicyclic compound is independently a five- or six-membered saturated, unsaturated, or aromatic ring, and the fused ring of the aza-fused bicyclic compound contains 1 to 5 nitrogen atoms, and the fused ring is an unsubstituted ring or a ring substituted with 1 or 2 substituents having 1 to 3 carbon atoms.

[0010] In the perovskite solar cell, the aza-fused bicyclic compound is preferably selected from the group consisting of pteridine, 1,5,7-triazidobicyclo(4.4.0)dec-5-ene, quinazoline, quinoline, 1,5-diazabicyclo[4.3.0]-5-nonene, imidazo[1,2-a]pyrimidine, 5,6,7,8-tetrahydroindolizine, 1-methyl-2,3-dihydro-1H-pyrrolidine and 2,4-dimethylquinoline.

[0011] In the above-mentioned perovskite solar cell, the acid ion in the organic salt is preferably selected from one of acid ions including O, S, P, N, F, I, Br, Cl, C and H.

[0012] In the above-described perovskite solar cell, the acid ion is preferably selected from an acid ion derived from one of acetic acid, phosphoric acid, nitric acid, chloric acid, sulfonic acid, sulfuric acid, hydrofluoric acid, hydrochloric acid, hydrobromic acid, and hydroiodic acid.

[0013] In the perovskite solar cell, the passivation layer is preferably a layer formed by applying a poor solvent having a passivation agent dissolved therein onto the perovskite layer, the poor solvent being selected from at least one of toluene, chlorobenzene, dichlorobenzene, ethyl acetate, ethyl ether, benzene, anhydrous ethanol, isopropanol, butanol, chloroform, methyl butyrate, anisole, xylene, and mesitylene.

[0014] In the perovskite solar cell, the molar ratio between the perovskite in the perovskite layer and the passivation agent in the passivation layer is preferably 100-800, and may be 200-600 or 250-400.

[0015] As a result, by using the passivation agent, a perovskite solar cell with improved cell efficiency and stability can be obtained.

[0016] Another aspect of the present invention provides a power generating device using the above-mentioned perovskite solar cell, which can provide a power generating device with improved efficiency and stability.

[0017] Another aspect of the present invention provides a power consuming device that uses the above-mentioned perovskite solar cell, thereby providing a power consuming device with improved efficiency and stability.

[0018] Another aspect of the present invention provides a method of forming a passivation layer in a perovskite solar cell as described above, the method comprising the steps of: The method includes the steps of applying a perovskite precursor solution onto a layer carrying a perovskite layer, followed by directly applying an anti-solvent containing a passivating agent, followed by annealing; Here, the passivation agent comprises an aza-fused bicyclic compound and / or an organic salt formed from an aza-fused bicyclic compound and an acid, and each fused ring of the aza-fused bicyclic compound is independently a five- or six-membered saturated, unsaturated, or aromatic ring, and the fused ring of the aza-fused bicyclic compound contains 1 to 5 nitrogen atoms, and the fused ring is an unsubstituted ring or a ring substituted with 1 or 2 substituents having 1 to 3 carbon atoms.

[0019] In the above method, preferably, the aza-fused bicyclic compound is selected from one of pteridine, 1,5,7-triazidobicyclo(4.4.0)dec-5-ene, quinazoline, quinoline, 1,5-diazabicyclo[4.3.0]-5-nonene, imidazo[1,2-a]pyrimidine, 5,6,7,8-tetrahydroindolizine, 1-methyl-2,3-dihydro-1H-pyrrolidine and 2,4-dimethylquinoline.

[0020] In the above method, preferably, the acid ion in the organic salt is selected from one of the acid ions including O, S, P, N, F, I, Br, Cl, C and H.

[0021] In the above method, the acid ion is preferably selected from one of acid ions derived from acetic acid, phosphoric acid, nitric acid, chloric acid, sulfonic acid, sulfuric acid, hydrofluoric acid, hydrochloric acid, hydrobromic acid and hydroiodic acid.

[0022] In the above process, preferably, the anti-solvent is selected from at least one of toluene, chlorobenzene, dichlorobenzene, ethyl acetate, ethyl ether, benzene, absolute ethanol, isopropanol, butanol, chloroform, methyl butyrate, anisole, xylene and mesitylene.

[0023] In the above method, the concentration of the passivating agent in the poor solvent is preferably 0.1 to 10 mmol / mL.

[0024] In the above method, the molar ratio of the perovskite precursor in the perovskite precursor solution to the passivation agent in the poor solvent is preferably 200-8,000, and may be 800-1,600 or 1,000-1,200.

[0025] This makes it possible to form a passivation layer in a simpler manner, passivating the surface and grain boundaries of the perovskite structure from all directions, providing a perovskite solar cell with higher cell efficiency and stability. Effect of the Invention

[0026] The perovskite solar cell according to the present invention can improve the cell efficiency and stability, and the manufacturing method according to the present invention can provide the perovskite solar cell having the above-mentioned advantages in a simpler manner. [Brief description of the drawings]

[0027] [Figure 1] FIG. 1 is a schematic diagram of the structure of a perovskite solar cell. [Diagram 2] FIG. 1 is a structural schematic diagram of a perovskite structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] In order to make the technical problems, technical solutions and beneficial effects of the present invention clearer, the present invention will be described in more detail below in conjunction with the drawings and examples. It should be understood that the specific examples described herein are only for the purpose of interpreting the present invention, and are not intended to limit the present invention.

[0029] 1 Perovskite Solar Cells First, the perovskite solar cell of the present invention will be briefly described. As shown in FIG. 1, the perovskite solar cell of the present invention sequentially includes a first electrode layer 2, an electron transport layer 3, a perovskite layer 4, a passivation layer 5, a hole transport layer 6, and a second electrode layer 7. When light is irradiated onto the perovskite layer, the perovskite structure absorbs the energy of the photons to generate free electrons and holes (hereinafter, the electrons and holes may be collectively referred to as "carriers"). The generated free electrons and holes are conducted to the first electrode and the second electrode via the electron transport layer and the hole transport layer, respectively, to generate a voltage between the first electrode and the second electrode, thereby realizing the energy conversion between light and electricity. It should be noted that FIG. 1 is merely a schematic diagram of an embodiment in which a passivation layer 5 is formed on one side of the perovskite layer 4, but the present invention is not limited to this structure, and for example, the passivation layer 5 may be formed on either one side or both sides of the perovskite layer 4.

[0030] 1.1 Perovskite layer 4 The perovskite layer contains crystals with a perovskite structure, and has the crystal structure shown in Figure 2. The perovskite structure commonly used in solar cells may be represented as an ABX3 structure, where A is an ion having a certain size and positive charge, such as an ion of an alkali metal such as cesium, or an ion of a nitrogen-containing small molecule organic substance such as methylamine (CH3NH2) or formamidine (HNCHNH2), the B site is an ion of a transition metal element, such as an ion of Pb or Sn, and the X site is a halogen ion, such as an ion of Br or I.

[0031] It should be explained that in the general ABX3 structure, A fills the BX octahedron composed of B and X to form a lattice structure. Therefore, the A site cation has a size requirement, which is generally called the "tolerance factor", and the tolerance factor must be between 0.8-1.2. If the tolerance factor is too large or too small, it will significantly affect the stability of the lattice structure or the desired structure cannot be formed.

[0032] The instability of the perovskite structure is specifically related to deep and shallow level defects that exist during the manufacturing process of perovskite solar cells and the operation of the device, and these defects have a serious impact on the efficiency and long-term stability of the cell. Another cause of the instability of the calcium structure is that it is prone to hydrolysis when it comes into contact with water.

[0033] 1.2 Passivation layer 5 The passivation layer is a layer placed between the perovskite layer and the electron transport layer and / or the hole transport layer to improve the stability of the perovskite structure and the lifetime of the solar cell device, which contains a passivation agent.

[0034] The present inventors have found that the use of the following passivation agent is more effective in improving battery efficiency and extending battery life than conventional passivation agents: The passivation agent in the present invention comprises an aza-fused bicyclic compound and / or an organic salt formed from an aza-fused bicyclic compound and an acid, each fused ring of the aza-fused bicyclic compound is independently a five- or six-membered saturated, unsaturated or aromatic ring, and the fused ring of the aza-fused bicyclic compound contains 1 to 5 nitrogen atoms, and the fused ring is a ring without a substituent or a ring substituted with 1 or 2 substituents having 1 to 3 carbon atoms.

[0035] The substituent on the fused ring may be a hydrocarbon group, an alcohol group, an ether group, an ester group, an aldehyde group, a ketone group, a carboxyl group, a carbonyl group, an amide group, an imide group, or a combination thereof. Specific examples thereof include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, a carbinol group, an alcohol group, an n-propanol group, an isopropanol group, a methyl ether group, an ethyl ether group, a propyl ether group, a methyl ester group, an ethyl ester group, a propioester group, a formaldehyde group, an acetaldehyde group, a propionaldehyde group, a methyl ketone group, an ethyl ketone group, an acetone group, a formic acid group, an acetic acid group, a propionic acid group, a formamide group, an acetamide group, and a propionamide group.

[0036] For example, when formamidine is used at the A site, formamidine is an organic component, and high temperatures due to direct sunlight and non-radiative recombination due to defects both lead to device temperature rise, causing formamidine volatilization and causing A site defects. Many conventional interface passivators form two-dimensional structures, which prevent A site cations from volatilizing, but the A site may be displaced and form multiple defects. The increased defects capture carriers such as free electrons or holes, which causes an increase in the internal resistance of the device, making carrier extraction difficult and reducing the short circuit current. In addition, the decomposition of perovskite causes a decrease in device stability. Therefore, passivation using conventional passivators is not very effective in improving the long-term stability of the device.

[0037] In the present invention, the passivation agent containing an aza-fused bicyclic compound and / or an organic salt formed therefrom with an acid is employed to passivate perovskite grain boundaries and surface defects.

[0038] The nitrogen atoms on the rings of the aza-fused bicyclic compounds and / or the organic salts formed therefrom with acids in the passivation agent of the present invention have strong proton binding ability and form a strong chemical bond with the A site, thereby preventing the decomposition or volatilization of the A site cations due to various reasons, making it difficult for harmful hydrogen vacancies to occur during use, and improving the stability of passivation and the efficiency of the device.

[0039] Specific examples of the aza-fused bicyclic compound include the substances used in the Examples, but the present invention is not limited to these compounds.

[0040] Although the principle is not yet clear, it can be presumed that, compared with the prior art, the compound used in the present invention has an increased number of rings, which improves the hydrophobicity of the material and can be introduced as a hydrophobic functional group, thereby significantly improving the water stability of the perovskite. In addition, the nitrogen on the aza ring and the A site of the perovskite have strong proton binding energy, which can suppress the loss of A site ions, thereby enhancing the passivation effect.

[0041] The acid ion in the organic salt formed with the above compound is selected from one of the acid ions including O, S, P, N, F, I, Br, Cl, C and H.

[0042] Specifically, the acid ion is selected from acid ions derived from one of acetic acid, phosphoric acid, nitric acid, chloric acid, sulfonic acid, sulfuric acid, hydrofluoric acid, hydrochloric acid, hydrobromic acid, and hydroiodic acid.

[0043] The acid ion is preferably derived from one selected from hydrofluoric acid, hydrochloric acid, hydrobromic acid, and hydroiodic acid, because when a halogen is selected and used as the acid ion, it can compensate for halogen vacancies on the perovskite surface. The acid ion is preferably derived from hydrofluoric acid, because it can compensate for defects in the X site and form hydrogen bonds with the A site cation to stabilize the A site cation.

[0044] The acid ions are preferably derived from one of the acids containing oxygen, sulfur, phosphorus, etc., such as one of carboxylic acid, sulfonic acid, sulfuric acid, and phosphoric acid, because the acid ions derived from these acids can form hydrogen bonds with the ions in the A site and anchor the ions in the B site, thereby stabilizing the ions in the A site and the B site, and further stabilizing the perovskite structure, thereby achieving the effect of improving the long-term stability of the battery device.

[0045] In the above perovskite solar cell, the molar ratio of the perovskite in the perovskite layer to the passivation agent in the passivation layer (molar amount of perovskite / molar amount of passivation agent) is preferably 100 to 800, and may be 200 to 600 or 300 to 400. If the amount of the passivation agent is too small relative to the perovskite, the defects of the perovskite structure cannot be sufficiently passivated, and ideal hydrophobicity cannot be imparted. If the amount of the passivation agent is too large, the effect of passivation reaches saturation, reducing the cost-effectiveness ratio, and may also have adverse effects such as interference with carrier transport, increased internal resistance, and even battery failure.

[0046] 1.3 Electron Transport Layer 3 and Hole Transport Layer 6 The electron transport layer and the hole transport layer are layers on both sides of the perovskite layer and the passivation layer, respectively, for transporting the free electrons and holes generated on the perovskite layer. By separating the electrons and holes and transporting them to the first electrode and the second electrode, the decrease in conversion efficiency caused by the recombination of the holes and electrons is avoided. It should be noted that FIG. 1 shows only one possible embodiment of the present invention, and the positions of the electron transport layer and the hole transport layer of the present invention may be interchanged.

[0047] At least one of the electron transport layer and the hole transport layer has a light transmittance in the visible light wavelength range of 50% or more, 60% or more, 70% or more, 80% or more, 90% or more, or 95% or more.

[0048] As the electron transport layer, the layer is made of a common electron transport material, and those skilled in the art can appropriately select it within the range that is advantageous for conversion efficiency. For example, tin oxide, titanium oxide, PCBM, C60 may be used, and tin oxide is preferably used. In addition, the method of manufacturing the layer can be appropriately combined with common methods such as coating, deposition, and annealing.

[0049] As the hole transport layer, the layer is made of a common hole transport material, and those skilled in the art can appropriately select it within the range that is advantageous for conversion efficiency. For example, PTAA, spiro, PEDOT:PSS can be used, and preferably spiro is used. In addition, the manufacturing method of the layer can be appropriately combined with common methods such as coating, deposition, and annealing.

[0050] 1.4 First electrode 2 and second electrode 7 The first electrode is laminated in a direction opposite to the direction of the perovskite layer of the electron transport layer, and is an electrode that guides electrons conducted from the electron transport layer to the outside for use. The second electrode is laminated in a direction opposite to the direction of the perovskite layer of the hole transport layer, and is an electrode that guides holes conducted from the hole transport layer to the outside for use. It should be noted that FIG. 1 shows only one possible embodiment of the present invention, and the positions of the first electrode and the second electrode of the present invention may be interchanged.

[0051] When the first electrode and the second electrode are opaque electrodes, they may be made of common materials for electrodes, and those skilled in the art can appropriately select them within a range that is favorable for conversion efficiency. For example, gold, silver, copper, aluminum, etc. may be used, and gold is preferably used. In addition, the method of manufacturing the layer may be appropriately combined with common methods such as coating, deposition, and annealing.

[0052] At least one of the first electrode and the second electrode is a transparent electrode, and the light transmittance of the transparent electrode in the visible light wavelength region is 50% or more, 60% or more, 70% or more, 80% or more, 90% or more, or 95% or more. When the electrode is transparent, it may be made of a common material for transparent electrodes, and a person skilled in the art can appropriately select the material within a range that is advantageous for conversion efficiency. For example, conductive oxides, metal grids, ultra-thin metal layers, metal nanowires, carbon-based transparent materials, polymers, etc. may be used. In view of high light transmittance, conductive oxides are preferably used. In addition, the electrode can be manufactured by appropriately combining common methods such as coating, deposition, and annealing.

[0053] 1.5 Base 1 If necessary, a base may be further provided on the outside of the first electrode and / or the second electrode, which is used to support the entire perovskite solar cell and facilitate operation and assembly.

[0054] The base may be an organic or inorganic flexible material such as polyimide (PI), polybutylene terephthalate (PET), polyamide (PA), polycarbonate (PC), ultra-thin glass, or a rigid material such as a glass plate or a metal plate.

[0055] When the first electrode and the second electrode each have a base on the outside thereof, at least one of the bases has a light transmittance in the visible light wavelength range of 50% or more, 60% or more, 70% or more, 80% or more, 90% or more, or 95% or more, and the translucent base is disposed on one side of the transparent electrode.

[0056] Also, when the first electrode and / or the second electrode have sufficient capacity to support the perovskite solar cell, the base may be omitted.

[0057] 2 How perovskite solar cells are manufactured The method for producing a perovskite solar cell of the present invention includes the steps of: The method includes applying a perovskite precursor solution onto a layer carrying a perovskite layer (step 1), directly applying a poor solvent containing the passivation agent onto the perovskite precursor solution layer (step 2), and annealing (step 3). Here, the application in steps 1 and 2 can be performed by a general method such as spin coating, blade coating, roll coating, or spray coating, but from the viewpoint of being able to control the thickness well, spin coating is preferably used.

[0058] This manufacturing method can simplify the manufacturing steps of the passivation layer, avoid the influence of multiple annealing on the perovskite structure, and realize the passivation during the process of forming the perovskite structure.

[0059] Specifically, the method of the present invention requires fewer annealing processes than the prior art, which can avoid multiple annealing of perovskite, save time costs, and improve manufacturing efficiency.

[0060] And in the method of the present invention, when the perovskite phase is not stable, a passivator is added, which can better bond with the perovskite at the grain boundaries and surface, and further stabilize the perovskite phase.

[0061] The passivation agent is not only present on the surface of the perovskite layer, but can also penetrate deep into the grain boundaries, so that the grain boundaries and the surface can be passivated simultaneously, realizing passivation in all directions. In this way, the recombination of electrons and holes at the grain boundaries and the surface can be more effectively prevented. And even if the grain boundaries are small, the method of the present invention can be used to allow the passivation agent, which has a large molecular volume, to penetrate deep into the grain boundaries. At the same time, since the passivation agent is present only in the poor solvent, the passivation agent does not affect the formation of the perovskite structure. In this regard, it is difficult to achieve with the conventional technology.

[0062] 2.1 Perovskite precursor solution The perovskite precursor solution includes a perovskite precursor and a solvent. Specifically, the perovskite precursor is a material containing A ions, B ions and X ions. The perovskite precursor solution can be, for example, a mixture of BX2 and AX in a solvent. Here, A can be selected from alkali metals such as cesium or nitrogen-containing small molecule organic compounds such as methylamine and formamidine as described above, B is Sn or Pb, and X is a halogen.

[0063] The solvent in the perovskite precursor solution may be appropriately selected from currently commonly used solvents, as long as it can dissolve BX2 and AX, can be compatible with the poor solvent, and can be removed by heating. Those skilled in the art can select any appropriate combination from the conventional techniques to produce the perovskite precursor solution.

[0064] Regarding the molar ratio of BX2 to AX (BX2 / AX), from the viewpoint of being able to sufficiently form the perovskite layer structure, the ratio is 1 or more, 1.01 or more, 1.02 or more, 1.03 or more, 1.04 or more, or 1.05 or more, and from the viewpoint of cost saving, the ratio is 1.5 or less, 1.4 or less, 1.3 or less, 1.2 or less, or 1.1 or less.

[0065] In the perovskite precursor solution, the concentration of the perovskite precursor is used to adjust the thickness of the perovskite layer formed, and the ideal concentration is 0.2-5mmol / mL, 0.3-4mmol / mL, 0.4-3mmol / mL, or 0.5-2mmol / mL for the concentration of BX2. When the concentration is such, it is favorable for the formation of a preferred perovskite structure.

[0066] It should be explained that the tolerance factor of A ions must be 0.8-1.2, and if the volume of ions is too large and the tolerance factor exceeds 1.2, it will cause lattice deformation or be difficult to fill into the BX octahedral structure, which will lead to concerns that the perovskite structure cannot be formed. Even if the structure can be formed, it will cause the crystallization process of perovskite to be blocked, which will lead to the deterioration of perovskite crystal quality, the formation of excessive grain boundaries, the generation of deep level defects, the capture of carriers, and the deterioration of photoelectric conversion efficiency and stability.

[0067] When two or more kinds of A ions are contained, the tolerance factors are preferably all 0.8 to 1.2. This is because the presence of large molecules destroys the crystal structure as described above, and even if they are used as additives, the large structure causes poor crystal quality and makes it difficult to achieve good stability.

[0068] 2.2 A solution containing a passivating agent In this method, the solution containing a passivating agent includes a poor solvent and a passivating agent.

[0069] The poor solvent is a solvent for changing the perovskite precursor to a perovskite structure. The poor solvent in the present invention is a solvent in which the solubility of the perovskite precursor is low, and is selected from at least one of toluene, chlorobenzene, dichlorobenzene, ethyl acetate, ethyl ether, benzene, anhydrous ethanol, isopropanol, butanol, chloroform, methyl butyrate, anisole, xylene, and mesitylene. The poor solvent is preferably a mixed solvent formed by adding at least one second poor solvent selected from ethyl ether, benzene, anhydrous ethanol, isopropanol, butanol, chloroform, methyl butyrate, anisole, xylene, and mesitylene to at least one first poor solvent selected from toluene, chlorobenzene, dichlorobenzene, and ethyl acetate.

[0070] By adjusting the ratio of the first anti-solvent to the second anti-solvent in the anti-solvent, the solubility of the precursor in the anti-solvent can be adjusted, thereby controlling the precipitation rate and crystal size of the perovskite structure when the anti-solvent contacts the precursor in the precursor solution.

[0071] In the poor solvent, the ratio (volume) of the first poor solvent to the second poor solvent is 100:0 to 100:50, and preferably 100:0 to 100:10. When the poor solvents are mixed in such a ratio for production, the precipitation rate and crystal size of the perovskite structure can be advantageously controlled.

[0072] The poor solvent of the present invention contains the passivation agent of the present invention, and the description is omitted here. It should be noted that the passivation agent in the prior art can also be used in the method for forming the passivation layer of the present invention. The passivation agent in the prior art is used.

[0073] In the poor solvent, the concentration of the passivator is 0.1 to 10 mmol / mL, and may be 0.5 to 8 mmol / mL, 1 to 5 mmol / mL, or 2 to 3 mmol / mL. When it is within the above range, it is possible to easily control the content of the passivator in the passivation layer without affecting the precipitation of the perovskite structure.

[0074] The molar ratio (R) of the perovskite precursor in the perovskite precursor solution to the passivator in the poor solvent is 200 to 8000, and may be 800 to 1600 or 1000 to 1200. If the amount of the passivator is too small relative to the perovskite precursor, the defects in the perovskite structure cannot be sufficiently passivated, and ideal hydrophobicity cannot be imparted. If the amount of the passivator is too large, the passivation effect reaches saturation, reducing the cost-effectiveness ratio, and may also have adverse effects such as carrier transport obstruction, increased internal resistance, and even battery failure.

[0075] 2.3 annealing In the present invention, after the perovskite precursor solution and the poor solvent are applied, an annealing treatment is performed, during which the solvent and the poor solvent in the precursor solution volatilize, and the precursor precipitates to form a perovskite structure, forming a perovskite layer and a passivation layer, while the passivation agent passivates the grain boundaries and surface of the perovskite structure.

[0076] The conditions of the annealing treatment may be appropriately set according to the type of solvent used and the parameters of the annealing equipment, and are not particularly limited. However, from the viewpoint of obtaining a well-ordered perovskite structure, annealing may be performed at 80°C to 200°C for 10 minutes to 2 hours. For example, the annealing conditions in the examples described later may be adopted.

[0077] 3 Power generation equipment The power generating device of the present invention is a power generating device including the above-mentioned perovskite solar cell, and the perovskite solar cell may be one or more. The power generating device further includes a control system and a transport system. The power generating device of the present invention adjusts the electric energy generated from the above-mentioned solar cell to electric energy compatible with the power consuming device through the control system and the transport system. It should be noted that the term "including" in this context refers to the case where the power generating device and the solar cell are electrically connected.

[0078] 4 power consumption equipment The power consumption device of the present invention is a power consumption device including the perovskite solar cell, and the perovskite solar cell may be one or more. The power consumption device further includes a system that utilizes the electrical energy generated from the perovskite solar cell. The system that utilizes the electrical energy may be, for example, a system that converts electrical energy into kinetic energy, internal energy, light energy, chemical energy, or the like. It should be noted that the term "including" refers to the case where the power consumption device and the solar cell are electrically connected.

[0079] Working Example The following provides a detailed description of the embodiments of the technical solution of the present application. The following embodiments are provided to more clearly explain the technical solution of the present application, and are merely illustrative and do not limit the scope of protection of the present application.

[0080] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art, and the terms used herein are used only to describe specific examples and are not intended to limit the present application. The terms "including" and "having" and any variations thereof in the specification and claims of this application and the description of the drawings above are intended to cover non-exclusive "containing".

[0081] In the description of the embodiments of the present application, the terms "first", "second", etc. are used only for the purpose of distinguishing different objects, and should not be understood as expressing or suggesting relative importance, or implying the number, particular order, or primary / secondary relationship of the indicated technical features. In the description of the embodiments of the present application, "plurality" means two or more, unless otherwise specified.

[0082] When referring to an "embodiment" in this specification, it means that a particular feature, structure, or characteristic described in connection with the embodiment may be included in at least one embodiment of the present application. The appearances of this phrase in various places in the specification do not necessarily all refer to the same embodiment, nor are they mutually exclusive independent or alternative embodiments from other embodiments. As will be clearly and implicitly understood by those skilled in the art, the embodiment described in this specification can be combined with other embodiments.

[0083] In the description of the embodiments of the present application, the term "and / or" merely describes the relationship between related objects and indicates that three relationships may exist, for example, A and / or B can represent three cases: A alone, a combination of A and B, and B alone. In addition, the character " / " in this specification generally indicates that the related objects before and after are in an "or" relationship.

[0084] In describing the embodiments of the present application, the orientations or positional relationships indicated by technical terms such as "inside" and "outside" are based on the orientations or positional relationships shown in the drawings, and are intended for the convenience or simplification of the description of the embodiments of the present application, and are not to be understood as limiting the embodiments of the present application, since they do not indicate or imply that the referenced devices or elements have a particular orientation or are constructed or operated in a particular orientation.

[0085] Although the examples of this application only show perovskite solar cells with a general structure, the present invention may also be applied to perovskite solar cells with an inverted structure. EXAMPLES

[0086] Perovskite solar cell manufacturing Example 1 [Fabrication of the electron transport layer] A 15% tin oxide solution was mixed with deionized water in a ratio of 1:3 and stirred at room temperature for 1 h. 70 μL of the solution was spin-coated onto a conductive glass surface and heated at 150° C. for 15 min.

[0087] [Fabrication of perovskite and passivation layers] Perovskite solution was prepared by adding formamidine iodide and chloromethylamine as AX and lead iodide as BX2 at (BX2 / AX=1.05) to a mixed solution of DMF and DMSO (DMF:DMSO=4:1), magnetically stirring at room temperature for 1 h, and filtering for use. The final concentration of perovskite precursor in the solution is 1.5 mmol / mL of lead iodide. The passivation materials in Tables 1 and 2 below were dissolved in a poor solvent, and the conductive glass on which the electron transport layer had been spin-coated was irradiated with UV for 15 minutes. 60 μL of perovskite solution was added dropwise onto the glass, and 600 μL of poor solvent in which the passivation material had been dissolved was added, followed by annealing at 150 ° C for 1 h, thereby simultaneously forming a perovskite layer and a passivation layer, and finally forming a perovskite layer with a thickness of 500 nm and a passivation layer with a thickness of 2 nm. The ratio (molar ratio) of the amount of perovskite to the passivation agent was 300.

[0088] [Fabrication of the hole transport layer] Li-TFSI, tBP, and FK209 were added to spiro, stirred for 1 h, and filtered to prepare for use. 60 μL of spiro was added dropwise to the conductive glass on which the perovskite layer and passivation layer had been formed, and spin-coated to form a hole transport layer.

[0089] [Manufacture of rear electrode] On the hole transport layer formed by spin coating, silver was deposited to a thickness of 80 nm in a vacuum deposition device by a conventional method to obtain a complete perovskite solar cell.

[0090] Examples 2 to 16 A perovskite solar cell was manufactured in the same manner as in Example 1, except that the conditions for forming the perovskite layer and the passivation layer were replaced with those shown in Tables 1 and 2.

[0091] Comparative Examples 1 to 3 A perovskite solar cell was manufactured in the same manner as in Example 1, except that the passivation agents shown in Tables 1 and 2 were added to the perovskite precursor solution and no passivation agent was added to the poor solvent.

[0092] Comparative Example 4 A perovskite solar cell was manufactured in the same manner as in Example 1, except that no passivation agent was added.

[0093] [Table 1]

[0094] [Table 2]

[0095] Battery characteristic test (IV test) For 20 solar cells of each of the examples and comparative examples obtained by the above method, an IV test was performed at 25°C and one irradiation intensity using a solar simulator from ENLITECH, and the average test results of the solar cells of each of the examples and comparative examples are shown in Table 3 below.

[0096] [Table 3]

[0097] Stability testing Twenty solar cells for each of the Examples and Comparative Examples obtained by the above method were stored in a humidity-controllable glove box, and aged for 30 days under conditions of a constant temperature of 25°C and a constant humidity of 60% RH to perform a stability test. The average IV test results, efficiency retention rate, number of damaged batteries and damage rate for each of the Examples, Comparative Examples and Reference Example that were not damaged after the stability test are shown in Table 4 below.

[0098] [Table 4]

[0099] As can be seen from the results of Tables 3 and 4 above, the perovskite solar cell using the passivation agent of the present invention has a more significant effect in improving device efficiency and stability than one not using the passivation agent of the present invention, the cell not passivated has a significant decrease in cell efficiency after being left for a certain period of time, and when the cation is the same, the use of an organic acid containing elements such as O, S, P, and N as the acid ion has a higher passivation effect. And the cell damage rate of the perovskite solar cell using the passivation agent of the present invention after being left for a certain period of time is significantly suppressed.

[0100] It has also been discovered that the perovskite solar cell obtained by using the method for preparing the passivation layer and perovskite layer of the present invention can avoid the need to heat and anneal the perovskite twice, and has higher device stability than that obtained by not using the method of the present invention, and the passivation material can be added under wet film conditions to control the crystallinity, so that the passivation material can be better filled into the grain boundaries and surfaces, better protecting the perovskite and enhancing the stability of the perovskite. [Industrial Applicability]

[0101] The present invention provides a perovskite solar cell with high energy conversion efficiency and excellent stability, and a method for manufacturing the solar cell, which is of great significance for responding to climate change and building an eco-civilization. [Explanation of symbols]

[0102] 1: base, 2: first electrode, 3: electron / hole conducting layer, 4: perovskite layer, 5: passivation layer, 6: hole / electron conducting layer, 7: second electrode

Claims

1. A perovskite solar cell, comprising: a photocatalytic device comprising at least an electrode, an electron transport layer, a hole transport layer, a perovskite layer, a passivation layer, and an optional base layer, the passivation layer containing a passivation agent, the passivation agent comprising an aza-fused bicyclic compound and / or an organic salt formed from the aza-fused bicyclic compound and an acid, each fused ring of the aza-fused bicyclic compound is independently a five- or six-membered saturated, unsaturated or aromatic ring, and the fused ring of the aza-fused bicyclic compound contains 1 to 5 nitrogen atoms; The perovskite solar cell, characterized in that the fused ring is a ring with no substituent, or a ring substituted with one or two substituents having 1 to 3 carbon atoms.

2. 2. The perovskite solar cell of claim 1, wherein the aza-fused bicyclic compound is selected from the group consisting of pteridine, 1,5,7-triazidobicyclo(4.4.0)dec-5-ene, quinazoline, quinoline, 1,5-diazabicyclo[4.3.0]-5-nonene, imidazo[1,2-a]pyrimidine, 5,6,7,8-tetrahydroindolizine, 1-methyl-2,3-dihydro-1H-pyrrolidine, and 2,4-dimethylquinoline.

3. 3. The perovskite solar cell according to claim 1, wherein the acid ion in the organic salt is selected from one of acid ions including O, S, P, N, F, I, Br, Cl, C, and H.

4. 4. The perovskite solar cell of claim 3, wherein the acid ions are selected from acid ions derived from one of acetic acid, phosphoric acid, nitric acid, chloric acid, sulfonic acid, sulfuric acid, hydrofluoric acid, hydrochloric acid, hydrobromic acid, and hydroiodic acid.

5. the passivation layer is a layer formed by applying a poor solvent having the passivation agent dissolved therein onto the perovskite layer, The perovskite solar cell according to any one of claims 1 to 4, characterized in that the poor solvent is selected from at least one of toluene, chlorobenzene, dichlorobenzene, ethyl acetate, ethyl ether, benzene, absolute ethanol, isopropanol, butanol, chloroform, methyl butyrate, anisole, xylene, and mesitylene.

6. 6. The perovskite solar cell according to any one of claims 1 to 5, wherein the molar ratio of the perovskite in the perovskite layer to the passivation agent in the passivation layer is from 100 to 800, and optionally from 200 to 600 or from 250 to 400.

7. A power generating device comprising the perovskite solar cell according to any one of claims 1 to 6.

8. A power consuming device comprising the perovskite solar cell according to any one of claims 1 to 6.

9. A method for producing a perovskite solar cell, comprising the steps of: applying a perovskite precursor solution onto a layer bearing a perovskite layer, followed directly by applying an anti-solvent containing a passivating agent, followed by annealing; the passivation agent comprises an aza-fused bicyclic compound or an organic salt formed from the aza-fused bicyclic compound and an acid; each fused ring of the aza-fused bicyclic compound is independently a five- or six-membered saturated, unsaturated, or aromatic ring, and the fused ring of the aza-fused bicyclic compound contains 1 to 5 nitrogen atoms; The method for producing a perovskite solar cell is characterized in that the fused ring is an unsubstituted ring or a ring substituted with one or two substituents having 1 to 3 carbon atoms.

10. 10. The method of claim 9, wherein the aza-fused bicyclic compound is selected from the group consisting of pteridine, 1,5,7-triazidobicyclo(4.4.0)dec-5-ene, quinazoline, quinoline, 1,5-diazabicyclo[4.3.0]-5-nonene, imidazo[1,2-a]pyrimidine, 5,6,7,8-tetrahydroindolizine, 1-methyl-2,3-dihydro-1H-pyrrolidine, and 2,4-dimethylquinoline.

11. 11. The method according to claim 9, wherein the acid ion in the organic salt is selected from the group consisting of O, S, P, N, F, I, Br, Cl, C and H.

12. 12. The method according to claim 11, wherein the acid ions are selected from the group consisting of acid ions derived from acetic acid, phosphoric acid, nitric acid, chloric acid, sulfonic acid, sulfuric acid, hydrofluoric acid, hydrochloric acid, hydrobromic acid, and hydroiodic acid.

13. The method according to any one of claims 9 to 12, wherein the poor solvent is selected from at least one of toluene, chlorobenzene, dichlorobenzene, ethyl acetate, ethyl ether, benzene, absolute ethanol, isopropanol, butanol, chloroform, methyl butyrate, anisole, xylene, and mesitylene.

14. The method according to any one of claims 9 to 13, wherein the concentration of the passivating agent in the poor solvent is 0.1 to 10 mmol / mL.

15. The method according to any one of claims 9 to 14, characterized in that the molar ratio of the perovskite precursor in the perovskite precursor solution to the passivation agent in the anti-solvent is 200 to 8000, and may be 800 to 1600 or 1000 to 1200.

Citation Information

Patent Citations

  • Two-dimensional carbon-based perovskite solar cell based on aminoquinoline ionic liquid

    CN110491996A

  • Preparation method and application of organic small molecular functional material taking pyrrolopyrrole as core structure

    CN111333654A

  • Method for passivating perovskite film layer and application of perovskite film layer in solar cell

    CN113809240A

  • Photovoltaic device containing metal halide perovskite and passivating agent

    JP2017501576A

  • Photoelectric conversion element, photoelectric conversion module, electronic apparatus, and power supply module

    JP2021093528A